India - a lead market for frugal innovations? Extending the lead market theory to emerging economies - Rajnish Tiwari; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2012)
India has emerged as a vibrant and versatile source for cost effective, disruptive innovations of various varieties. Price-sensitive consumers in a large and growing market keep inducing firms to apply frugal engineering for creating affordable products and services without compromising excessively on quality. Because, as The Economist asserts: Frugal does not mean second-rate. Such innovations are characterized by high affordability, robustness, and good enough quality in a volume-driven market. Resource constraints motivate firms and entrepreneurs to think out-of-the-box. The trick lies in creating solutions that are able to circumvent given environmental constraints in a cost effective way. India's large and enormously young population faced with limited budgets, but well-endowed with high aspirations, provides an ideal experiment ground for many firms. Solutions created for the Indian market are often suitable for other developing countries in Asia, Africa and Latin America that frequently face similar socio-economic conditions. In some instances they succeed even in developed country markets by enabling significant cost reductions. This emergence as a hub for frugal innovations possibly suggests a lead market role for India. On the other hand, lead markets, as understood today, are characterized by high per capita income, great customer sophistication and high quality infrastructure. Such assumptions imply that lead markets, almost by default, can only exist in economically developed countries because only they can finance the development effort. Using two anchor-cases of product innovations aimed at price-sensitive segments in India we generate preliminary evidence to challenge some of the core assumptions of the lead market theory and propose that lead markets can emerge in developing countries too because market attractiveness (e.g. volume of demand, export possibilities) and technological capabilities are able to offset many other deficiencies. The supposed absence of customer sophistication is channelized into a challenge for supplier-side sophistication to design cost effective, good enough solutions (low-cost, thin-margin) that can meet the aspirations of consumers in a highly competitive market. In order to master this challenge companies need access to a competent and sufficiently large technical base with first-hand knowledge of the ground situation of targeted customer groups (social capital).
urn:nbn:de:gbv:830-tubdok-11371
Keywords: 650; Lead Markets; Frugal Innovations; India; Globalization of Innovation; Internationalization of R&D